2013
DOI: 10.5751/es-05549-180305
|View full text |Cite
|
Sign up to set email alerts
|

REDD+ and Human Rights: Addressing Synergies between International Regimes

Abstract: ABSTRACT. The making of the REDD+ mechanism in the framework of the United Nations Framework Convention on Climate Change (UNFCCC) has raised specific concerns on how to reconcile incentives for forest carbon sequestration with the protection of the rights of the numerous communities that rely upon forests for their livelihood, shelter, and survival. Although the nascent REDD+ mechanism provides an opportunity to provide multiple benefits, the design of a framework to secure such benefits and avoid perverse ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
(13 reference statements)
0
24
0
1
Order By: Relevance
“…There is, however, a difference between internal self-determination (indigenous people have the rights to choose their political allegiances, to influence the political order in which they live, and to preserve their cultural, ethnic, historical, or territorial identity) and external self-determination (indigenous people have the right to determine their future international status and liberate themselves from existing rules, or the creation of an independent state); FPIC refers to the first and not to the second [35,36]. Moreover, many states engaged in REDD+ implementation have also ratified global and regional human rights treaties [37] that require them to respect and take positive measures to fulfill rights and protect subjects within their jurisdiction against violations carried out by third parties [38]. The right to FPIC, therefore, is directly linked to a state's obligation to uphold indigenous people's rights in the pursuit of their political commitment to those international treaties [30].…”
Section: The Political Context Of Fpic In Vietnammentioning
confidence: 99%
“…There is, however, a difference between internal self-determination (indigenous people have the rights to choose their political allegiances, to influence the political order in which they live, and to preserve their cultural, ethnic, historical, or territorial identity) and external self-determination (indigenous people have the right to determine their future international status and liberate themselves from existing rules, or the creation of an independent state); FPIC refers to the first and not to the second [35,36]. Moreover, many states engaged in REDD+ implementation have also ratified global and regional human rights treaties [37] that require them to respect and take positive measures to fulfill rights and protect subjects within their jurisdiction against violations carried out by third parties [38]. The right to FPIC, therefore, is directly linked to a state's obligation to uphold indigenous people's rights in the pursuit of their political commitment to those international treaties [30].…”
Section: The Political Context Of Fpic In Vietnammentioning
confidence: 99%
“…Therefore, the programme represents an unprecedented opportunity to enhance forest governance and strengthen global conservation efforts. Scholars found that nearly all the REDD+ implementing countries have weak governance structures however, exhibit a political commitment to REDD+ but have powerful drivers for deforestation, weak multilevel governance, low cross-sectoral horizontal coordination, and lack of technical and administrative capacity [28,29,35]. Wertz-Kanounnikoff and Angelsen [36] added that national policy and legal frameworks are crucial in accounting for and controlling deforestation and forest degradation, managing REDD+ programme, and building a strong sense of ownership among the beneficiaries.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the similarity of principles and criteria due to the existence of different initiatives, host countries require a huge amount of effort in order to adopt and consolidate multiple initiatives (Savaresi 2013). To avoid cumbersome procedures and rising costs, it is important to decide on initiatives that are based on a partnership with international forest certification systems or countermeasures against illegal logging, and coordinated in the international community, or select initiatives that formulate agreements in many countries (Greenpeace 2012, McDermott et al 2012, Moss & Nussbaum 2011, Pro Forest 2010, Roe et al 2013, Savaresi 2013, Silori et al 2013. And to share the benefits and opportunities created by REDD+, it is also important to clearly design and coordinate national and international level projects, with strong but suitable compliance systems (FCMC 2012).…”
Section: Issues For Development Of Effective Social Safeguardsmentioning
confidence: 99%